Nilai Kajian Kepercayaan Masyarakat Terhadap Cerita Puyang Serunting di Desa Rantau Panjang Kecamatan Semidang Alas Kabupaten Seluma Kajian Antropologi Sastra - Selfia, Ana; Khermarinah, Khermarinah; Sari, Wenny Aulia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This study aims to explore the values of community beliefs regarding the legend and grave of Puyang Serunting in Rantau Panjang Village, as well as the functions of these beliefs within the community. The research employs a descriptive qualitative method, utilizing both primary and secondary data. Data collection techniques include observation, interviews, and documentation. The findings reveal five functions of the belief system: 1) reinforcing religious emotions; 2) serving as a system of imaginary projection; 3) acting as an educational tool for children or adolescents; 4) providing a rational folk explanation for incomprehensible natural phenomena; and 5) offering comfort to those affected by misfortune. The study identifies four key values of community beliefs: 1) religious value; 2) customary value; 3) traditional value; and 4) social value. Among these, social value is the most prominent, as it aligns with the legend of Puyang Serunting Sakti, also known as “Si Pahit Lidah” (The Bitter Tongue), whose mystical power makes his words come true. The belief in his powers has fostered social cohesion and remains influential to this day, reinforcing other values such as customs, traditions, and religious practices within the community. In conclusion, the people of Rantau Panjang Village believe in the legend and grave of Puyang Serunting Sakti through customary, traditional, and social values, with social value being the most dominant as it strengthens community bonds. This belief system functions to reinforce religious emotions, educate children, explain natural phenomena, and provide comfort in times of misfortune. Keywords: Serunting Sakti legend, Community Beliefs, Grave.